EVALUATION OF THE CEARÁ FAMILY MEDICAL PROGRAM: A CROSS-SECTIONAL STUDY - Messias, Kelly Leite Maia de; Simões, Luiza Lúlia Feitosa; Bessa, Olívia Andréa Alencar Costa (Cadernos ESP, 2022)
To assess the first level (satisfaction) by measuring social actors - managers of Primary Health Care Units, teachers, learners, and users participated in the Ceará Family Medical Program (PMFC). The evaluation was based on the Kirkpatrick Model for the different actors involved. Data collection instruments were created via electronic forms and the actors’ satisfaction was measured. Most managers fully agree with proper professional practice, interpersonal/team relationship, and the importance of the PMFC. Most teachers fully agree with the importance of the activities and relevance of PMFC. More than half of the students fully agree with the importance of the activities and relevance of teachers.  The evaluation is one of the foundations for amplifying the effectiveness of health care actions, supporting improvements in quality of life, health, and social development.
Keywords: Process Assessment, Health Care; Educational Measurement; Evaluation Studies as Topic; Family Health Strategy